Exploration Of Socio-Political Change In Natural Resource Management In Urban Areas - Irawanto Irawanto; Muhammad Mochtar Mandala Silam; Nurmalasyiah Nurmalasyiah (Journal of Politica Governo, 2025)
Rapid urbanization in major cities has put great pressure on natural resources, leading to environmental degradation, reduced green space, and increased pollution and carbon emissions. This process led to a major change in the way societies managed natural resources, affecting their quality and availability. This study explores the influence of socio-political changes on urban natural resource management, with a focus on social dynamics, government policies, and the role of civil society and the private sector. The findings show that the imbalance between urban development and the preservation of natural resources often fuels conflict, while adaptive policies, green technologies, and nature-based approaches can be solutions to reduce environmental impacts. The study also identified that community participation and collaboration between sectors are essential to address the challenges of sustainable natural resource management. This collaboration will improve the efficiency of resource use and reduce negative impacts on the environment, ensuring the sustainability of natural resources for the future.